India 2000, perspectives of a near future - Rothermund, Dietmar (Asien, 1984)
The author traces the trend of development in agriculture and industry, looks at urbanization and the problems of a deteriorating environment and assesses the potential performance of the political system. Intensification of agriculture is necessary as the area under cultivation cannot be extended any longer. (DÜI-Sen)